Swedish dairy farmers’ perceptions of animal welfare inspections - Lundmark Hedman, Frida; Rodriguez Ewerlöf, Ivana; Frössling, Jenny; Berg, Charlotte (Frontiers in Animal Science, 2022)
Farmers today must comply with animal welfare legislation and often one or more private standards. This makes the number of regulations quite comprehensive and the control arena more complex, with several different animal welfare inspections and audits taking place at farm level. This study investigated perceptions among dairy farmers in Sweden of the official animal welfare inspections and the private Arla and KRAV audits, both separately and in relation to each other, and examined associated factors that could potentially influence their perceptions. An electronic questionnaire was developed and answered by 216 Swedish dairy farmers during spring 2021. The respondents in general acknowledged the need for animal welfare inspections, but had rather diverse perceptions of the actual inspections and inspectors, reporting both positive and negative experiences. They reported more negative experiences of official and Arla inspections than of KRAV (organic farming) inspections and most did not believe that inspections had improved animal welfare on their farm. Most of the respondents called for better coordination between the different inspection types. Most farmers reported being very worried before an official or Arla inspection, which was related to their more negative perceptions of these inspections. Other factors associated with farmers’ perception of the inspections were e.g., acceptance of a regulation, the perceived necessity of an inspection, satisfaction with the inspector’s competence, manner, and behavior, perceived fairness of treatment, and whether non-compliances were recorded. The farmers perceived official inspections as more negative if the inspector was a young woman, if there was more than one inspector present, and if the inspection was not pre-announced. These findings indicate a need for objective and accurate communication regarding different animal welfare regulations and inspections. To achieve greater trust and lower concerns among farmers about animal welfare inspections, all stakeholders need to be involved in communication.